Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan Bagian Produksi PG. Meritjan Kediri. - Isvandiari, Any; Fuadah, Lutfiatul (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
The research aims to know the effect of compensation variable and work discipline on the performance of the production employees PG. Meritjan Kediri, either partially or simultaneously. The data collected by distributing questionnaires, research conducted on 77 respondents production, samples from the production employees PG. Meritjan Kediri. By using a likert scale,the answer of respondentsbe treated used double regression analysis, t test, F test and R2 test. The results of this study found that there was a significant effect (significant) partially between the variables of compensation and work discipline variables on the dependent variable, and no influence employee performance variables simultaneously study consisted of compensation and work discipline on employee performance. From the results found in this study that the leaders should pay attention to PG. Meritjan Kediri compensation, work discipline and supervise all activities of employees to improve employee performance Part Production PG. Meritjan Kediri